Third-Country Effects of Regional Trade Agreements : A Firm-Level Analysis - Lee, Woori (World Bank, Washington, DC, 2019)
Do regional trade agreements negatively impact non-members? This paper revisits this long-standing trade policy question using firm-level data and detailed information on the content of trade agreements. Differently from the conventional view on trade diversion, the analysis identifies a positive spillover effect of regional trade agreements: they increase the probability of export and entry of third-country firms that previously exported to one of the member countries. This spillover effect is driven by deeper trade agreements, as they make member countries more "similar" in terms of the regulatory environment. Indeed, firms exporting regulation-intensive products benefit disproportionately more from deep trade agreements in destination markets, especially if the agreement includes nondiscriminatory provisions and addresses regulatory issues.